2015
DOI: 10.1186/s12890-015-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and nitric oxide signaling related biomarkers in patients with pulmonary hypertension: a case control study

Abstract: BackgroundOxidative stress (OS) and reduced nitric oxide (NO) bioavailability contribute to the pathogenesis of pulmonary hypertension (PH). Whether there are associations between OS and NO signaling biomarkers and whether these biomarkers are associated with the severity of PH remain unclear.MethodsBlood samples were collected from 35 healthy controls and 35 patients with pulmonary arterial hypertension (PAH, n = 12) or chronic thromboembolic pulmonary hypertension (CTEPH, n = 23). The mean pulmonary artery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
0
47
1
1
Order By: Relevance
“…Its content reflects the severity of free radical attack on cells. The results showed that the MDA content was lower in patients with hypertension and hypertensive ischemic stroke [32]. OPO could decrease MDA activity, thus reducing hypertension.…”
Section: Discussionmentioning
confidence: 88%
“…Its content reflects the severity of free radical attack on cells. The results showed that the MDA content was lower in patients with hypertension and hypertensive ischemic stroke [32]. OPO could decrease MDA activity, thus reducing hypertension.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, a significant positive relationship was observed between mPAP and ADMA levels in patients with CHD‐PAH in our study ( r =.35, P =.05). The mPAP and PVR index were positively correlated with the ADMA level ( r =.762, P =.006; r =.603, P =.038, respectively) …”
Section: Discussionmentioning
confidence: 94%
“…Suppression of endothelial DDAH expression and function is suggested to be an important underlying mechanism in hypoxia‐induced PH . Staab et al reported increases in serum ADMA levels in lung tissue of a smoker and the decreases in total lung DDAH expression in lung tissue and cultured LA‐4 cells …”
Section: Discussionmentioning
confidence: 99%